Effects of water immersion on posttraining recovery in Australian footballers - Elias, G. P.; Varley, M. C.; Wyckelsma, V. L.; McKenna, M. J.; Minahan, C. L.; Aughey, R. J. (International Journal of Sports Physiology and Performance, 2012)
urpose: The authors investigated the efficacy of a single exposure to 14 min of cold-water immersion (COLD) and contrast water therapy (CWT) on posttraining recovery in Australian football (AF). Method: Fourteen AF players participated in 3 wk of standardized training. After week 1 training, all players completed a passive recovery (PAS). During week 2, COLD or CWT was randomly assigned. Players undertook the opposing intervention in week 3. Repeat-sprint ability (6 × 20 m), countermovement and squat jumps, perceived muscle soreness, and fatigue were measured pretraining and over 48 h posttraining. Results: Immediately posttraining, groups exhibited similar performance and psychometric declines. At 24 h, repeat-sprint time had deteriorated by 4.1% for PAS and 1.0% for CWT but was fully restored by COLD (0.0%). At 24 and 48 h, both COLD and CWT attenuated changes in mean muscle soreness, with COLD (0.6 ± 0.6 and 0.0 ± 0.4) more effective than CWT (1.9 ± 0.7 and 1.0 ± 0.7) and PAS having minimal effect (5.5 ± 0.6 and 4.0 ± 0.5). Similarly, after 24 and 48 h, COLD and CWT both effectively reduced changes in perceived fatigue, with COLD (0.6 ± 0.6 and 0.0 ± 0.6) being more successful than CWT (0.8 ± 0.6 and 0.7 ± 0.6) and PAS having the smallest effect (2.2 ± 0.8 and 2.4 ± 0.6). Conclusions: AF training can result in prolonged physical and psychometric deficits persisting for up to 48 h. For restoring physical-performance and psychometric measures, COLD was more effective than CWT, with PAS being the least effective. Based on these results the authors recommend that 14 min of COLD be used after AF training.